Development of bioorganic fertilizer containing Pseudomonas GanoEB3 in promoting oil palm growth and inhibiting Ganoderma boninense - Abdul Wahab, Nurul Isma (2014)
Oil palm is one of the important crops in Malaysia. Basal Stem Rot (BSR) disease is the biggest threat for oil palm production in Malaysia caused by Ganoderma boninense has been causing a huge damage for the oil palm industry in Malaysia. The objective of this study was to develop the bioorganic fertilizer containing Pseudomonas GanoEB3 as oil palm growth enhancer and for inhibiting Ganoderma boninense. Endophytic bacteria Pseudomonas GanoEB3 was isolated from healthy oil palm roots,and cultured on nutrient agar media. A suspension containing 108 CFU/mL of the bacteria cells being mixed with vermiculite powder and stored at room temperature. The vermiculite powder (V) containing Pseudomonas GanoEB3 has been formulated with Bioorganic EFB and Bioorganic BF with following ratios; 0 g (EFB/BF): 60 g (V), 10 g (EFB/BF): 50 g (V), 20 g (EFB/BF): 40 g (V), 30 g (EFB/BF): 30 g (V), 40 g (EFB/BF): 20 g (V), 50 g (EFB/BF): 10 g (V) and 60 g (EFB/BF): 0 g (V). This study found that 30 g Bioorganic EFB mixed with 30 g vermiculite containing Pseudomonas GanoEB3 showed the best viability test with the percentage inhibition of radial growth (PIRG) value of 57.75% against G. boninense after one day product storage. Whereas, the PIRG value was 14.38% after twelve months product storage. Meanwhile, 10 g Bioorganic BF mixed with 50 g vermiculite containing Pseudomonas GanoEB3 showed 53.75% and 18% PIRG value after one day and twelve months product storage, respectively. Plant growth result showed that seedlings treated with Bioorganic BF gave the highest result in plant height (91.61 ± 0.80 cm), girth (46.86 ± 0.49 mm), frond length (64.61 ± 0.58 cm),number of leaflets (17.67 ± 0.30), number of frond (14.33 ± 0.18), chlorophyll content (54.95 ± 0.47 μg/L), leaf area index (2175.30 ± 88.08 cm2) and biomass (53.97 ± 0.76 g) respectively, followed by seedlings treated with Bioorganic EFB and control treatment. Pathological analysis showed that Bioorganic EFB containing Pseudomonas GanoEB3 (T3) and Bioorganic BF containing Pseudomonas GanoEB3 (T4) also have a good potential in inhibiting the growth of G. boninense. The reduced percentage of disease incidence (DI) for T3 (40%) and T4 (50%), area under the disease progress curve (AUDPC) for T3 (42 units2) and T4 (76 units2), disease severity of foliar index (DSFI) for T3 (37.5%) and T4 (45%), disease severity of bole index (DSBI) for T3 (40%) and T4 (47.5%), disease severity of root index (DSRI) for T3 (55%) and T4 (52.5%) and dead seedlings for T3 (30%) and T4 (40%) compared with control treatment (T2). It shows that both treatments have a good potential in inhibiting BSR disease in oil palm seedlings. This study revealed that Bioorganic EFB and Bioorganic BF containing Pseudomonas GanoEB3 are suitable as an effective biological control agent for promoting the growth of oil palm seedlings and suppressing G. boninense.